"DNT LET 'EM H8 U!": Applying the routine activity framework to understand cyberhate victimization among adolescents across eight countries. (January 2021) - Wachs, Sebastian; Costello, Matthew; Wright, Michelle F.; Flora, Katerina; Daskalou, Vassiliki; Maziridou, Evdoxia; Kwon, Yeji; Na, Eun-Yeong; Sittichai, Ruthaychonnee; Biswal, Ramakrishna; Singh, Ritu; Almendros, Carmen; et al.
Abstract: Recent evidence shows that adolescents across the globe are increasingly encountering hateful material on the Internet. However, the factors that lead adolescents to fall victim to cyberhate are still not well understood. To address this gap in the literature and assist media education campaigns in developing theoretically-grounded prevention programs, the present study utilizes Routine Activity Theory to investigate whether witnessing cyberhate (exposure to motivated offenders), parental mediation of Internet use (capable guardianship), and adolescents' online disclosure of private information (target suitability) predict cyberhate victimization among adolescents. Participants consisted of 6829 adolescents ranging in age from 12 to 18 ( M age = 14.93; SD = 1.64) from Cyprus, Germany, Greece, India, South Korea, Spain, Thailand, and the United States. Results showed that witnessing cyberhate was positively correlated with cyberhate victimization. Further, instructive parental mediation was negatively associated with cyberhate victimization, while restrictive parental mediation demonstrated the opposite effect, suggesting that the form of parental mediation matters when attempting to reduce adolescents' risk for cyberhate victimization. Finally, online disclosure was positively associated with cyberhate victimization. Consequently, the present investigation confirms the usefulness of applying Routine Activity Theory to cyberhate victimization. Furthermore, the findings highlight the need for effective prevention programs. Based on the findings of this study, media education training that equips adolescents with the skills they need to manage cyberhate experiences, increase their critical attitudes about private information they share online, and inform parents to use effective mediation strategies to diminish dangers associated with cyberhate is suggested. Highlights: This study includes self-reports from 6829 adolescents across eight countries. We investigated whether witnessing cyberhate, parental mediation, and online disclosure predict cyberhate victimization. Witnessing cyberhate and online disclosure was positively associated with cyberhate victimization. Instructive mediation was negatively related with cybervictimization and restrictive mediation showed the opposite effect. Practical implications for the development of media education programs that prevent cyberhate will be discussed.